Northanger Abbey - Jane Austen (Edition libre / Open Library, 1817)
Austen's witty exploration of the perils of mistaking fiction for reality During an eventful season at Bath, young, naïve Catherine Morland experiences the joys of fashionable society for the first time. She is delighted with her new acquaintances: flirtatious Isabella, who shares Catherine's love of Gothic romance and horror, and sophisticated Henry and Eleanor Tilney, who invite her to their father's mysterious house, Northanger Abbey. There, her imagination influenced by novels of sensation and intrigue, Catherine imagines terrible crimes committed by General Tilney. With its broad comedy and irrepressible heroine, this is the most youthful and and optimistic of Jane Austen's works. For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,700 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators.
Droits : Métadonnées bibliographiques et couvertures référencées via Open Library / Internet Archive. Vérifier les droits de couverture selon usage final.
Keywords: gothique; satire; Austen; classique; Littérature